Prognostic impact of body composition and immune-nutritional status in oligometastatic NSCLC patients receiving radiotherapy - Huang, Zhifei; Guo, Ziwen; Gao, Bo; Li, Shun; Yu, Yaner; Zhu, Shuangqiu; He, Zelai; Chen, Haiyan; Jiang, Hao (Frontiers in Nutrition, 2025)
BackgroundMetabolic and nutritional status are recognized as prognostic and predictive biomarkers in cancer treatment. However, there is limited research on oligometastatic non-small cell lung cancer (NSCLC) patients undergoing radiotherapy. We aimed to explore the independent and synergistic effects of body composition and immune-nutritional status on survival outcomes in these patients.MethodsPatients with oligometastatic NSCLC who underwent radiotherapy between 2017 and 2022 were retrospectively included. The evaluated outcomes were overall survival (OS) and progression-free survival (PFS). The skeletal muscle index (SMI), subcutaneous fat index (SFI), and pericardial fat index (PFI) were obtained using computed tomography (CT) and normalized by height squared. Laboratory biomarkers were utilized to assess immune-nutritional status. Univariate chi-square tests and multivariate logistic regression analyses were employed to determine correlations between hematological parameters and body composition. We conducted K-M analyses, along with univariate and multivariate Cox regression analyses to evaluate survival outcomes.Results102 patients [mean age 61.44 years, 51 males (50%)] were included. Compared to non-responders, responders exhibited a significantly lower prevalence of sarcopenia (44.93 vs. 55.07%, P = 0.007) and demonstrated relatively better immune-nutritional scores. Logistic regression analyses revealed that a low Prognostic Nutritional Index (PNI) was a risk factor for SMI, SFI, and PFI. Multivariate Cox analyses revealed that C reactive protein-to-albumin ratio (CAR) (HR = 0.26; 95% CI 0.11–0.61; P = 0.002) and PFI (HR = 2.73; 95% CI 1.06–7.01; P = 0.037) were predictive factors for OS. CAR (HR = 0.34, P = 0.001) and SFI (HR = 1.82, P = 0.049) were independent prognostic markers for PFS. K-M analyses indicated that the group with high PNI and high SFI exhibited markedly improved OS and PFS, as well as the one with high PNI and without sarcopenia (P < 0.001).ConclusionAmong oligometastatic NSCLC patients receiving radiotherapy, higher skeletal muscle and fat content, along with better immune-nutritional status, correlated with improved survival outcomes.